Potensi Alocasia macrorhiza Sebagai Fitoremediator Logam Kromium - Wahyu Surakusumah; Tina Safaria Nilawati; Rizka Khairunisa (Jurnal Ilmu Alam dan Lingkungan, 2020)
Chromium and its compounds are widely used by several industries as raw material. Chromium when polluting the soil can have adverse effects on the environment and humans. One technique that can be used to remediate the quality of soil contaminated by chromium is the phytoremediation method. The purpose of this study was to identify the potential of Alocasia macrorrhiza as a phytoremediator chromium agent. The research was conducted in two stages consisting of media optimization stage and phytoremediation parameter measurement stage. The parameters measured consisted of plant biomass, chlorophyll content, physiological responses, factor translocation, factor biconcentration and factor tolerance. The results showed that Alocasia macrorrhiza has the potential as a phytoremediation agent for chromium-contaminated soils with concentrations less than 401 ± 0.02 ppm, has the ability to reduce chromium content in soils by 37.94% and the mechanism of metal chromium absorption through rhizofiltration.